Eversion endarterectomy under full prasugrel treatment. (10th November 2017) - Kotsis, Thomas; Christoforou, Panagitsa; Asaloumidis, Nikolaos; Argyra, Erifyli
The third-generation thienopyridine prasugrel has much stronger antiplatelet effect compared to other current antiplatelet inhibitors and exhibits practically zero resistance in healthy people. Prasugrel is used as a pre- and post-treatment in percutaneous coronary or neurovascular interventions with parallel aspirin regime. However, as there is a higher reported bleeding with intraluminal interventions and meticulous technique is recommended, there is nearly non-existent international experience of open surgery under full prasugrel treatment. We present, herein, a case of open carotid endarterectomy with the eversion technique in an asymptomatic patient with carotid stenosis, who was receiving dual antiplatelet therapy with aspirin and prasugrel, due to a previous insertion of two newer drug-eluting stents at the left anterior descending artery and the right coronary artery. The resistance test to prasugrel showed complete inhibition of platelet function. Open surgery was performed under continuation of prasugrel treatment and interruption of aspirin for 3 days before surgery. No perioperative and postoperative neurologic or cardiologic event occurred. No bleeding at the cervical or cerebral area was noted.